Rwanda : Second Review Under the Policy Support Instrument and Request for Modification of Assessment Criteria; Staff Report; Staff Supplement; Press Release. (IMF Staff Country Reports; Country Report ;, 2011)
Based on the economic developments and policies of Rwanda, the staff's report was prepared. The rising global food and fuel prices have begun to elevate inflationary shares. The authorities are streamlining expenditures and introducing further reforms in revenue administration and public financial management (PFM). Structural reforms in the financial sector and monetary policy have been introduced. The new exchange rate management framework also enhanced monetary policy implementation. The overall fiscal deficit is programmed to be higher than projected by 1\2 percent of GDP.